Barriers in maintaining oral health among the children with cerebral palsy - Parent/caregiver's perspective - Diana Constance; Rohini Subbiah; Aparna Sukumaran; Parangimalai Diwakar Madankumar (Wolters Kluwer Medknow Publications, 2023)
Background: Cerebral palsy (CP) is primarily a neuromotor disorder that affects the development of movement, muscle tone, and posture. Objective: This qualitative study explores the underlying barriers in maintaining oral health from the perspective of the caregivers or parents. Materials and Methods: Focus group discussion was conducted with the parents or caregivers in the National Institute for Empowerment of Persons with Multiple Disabilities (NIEPMD), Muttukadu, Chennai. Data were collected from seven participants. Thematic analysis identified key themes using NVivo software. Results: The discussion on barriers to maintain oral health faced by parents of children with CP identified a collation of three key themes: behavioral challenges, inhibited social and communication skills, and parental dependence. Conclusion: Oral health professionals should aim to raise awareness among health-care professionals to work toward reducing the barriers to oral health care that these populations currently experience.